The Sahabaverification of the Hadith narration in the time of the Caliphate - ben Mohammed, Abdelfattah Fayoud (Journal of Islamic Sciences, 2019)
In this research, I followed the integrated approach through which I tried to make use of the various scientific approaches that serve the subject, describing, comparing, documenting, analyzing, explaining, criticizing, and deriving The results of the research were: That the fear of the Sunnah of loss and misrepresentation after the death of the Prophet peace be upon him to make the adult period known as hardness in the receipt and performance, which established the rules of consideration in Sindh and Metn, and the research shows that the outbreak of sedition and the emergence of the causes of the Lying in this period had a positive impact on the Sunnah , The movement of modern criticism has grown, and its rules have been embraced.